2019
DOI: 10.1104/pp.18.01391
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene Acts as a Signaling Molecule in Gene Networks Important for Stress Responses and Plant Growth

Abstract: Isoprene synthase converts dimethylallyl diphosphate to isoprene and appears to be necessary and sufficient to allow plants to emit isoprene at significant rates. Isoprene can protect plants from abiotic stress but is not produced naturally by all plants; for example, Arabidopsis (Arabidopsis thaliana) and tobacco (Nicotiana tabacum) do not produce isoprene. It is typically present at very low concentrations, suggesting a role as a signaling molecule; however, its exact physiological role and mechanism of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
164
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 103 publications
(184 citation statements)
references
References 174 publications
(299 reference statements)
19
164
1
Order By: Relevance
“…Conversely, significant positive effects were recorded for dry weight under heat stress only. Indeed, our data are in line with most of the literature showing the efficacy of hemi-and monoterpenes at protecting the photosynthetic apparatus under high temperatures [25,30,34]. Somehow surprisingly, however, these results indicate relatively minor phenotypic variations consequent to VOCs' emission under the stress conditions tested.…”
Section: Isoprene and Ocimene Emission Resulted In A Moderate Toleransupporting
confidence: 91%
See 4 more Smart Citations
“…Conversely, significant positive effects were recorded for dry weight under heat stress only. Indeed, our data are in line with most of the literature showing the efficacy of hemi-and monoterpenes at protecting the photosynthetic apparatus under high temperatures [25,30,34]. Somehow surprisingly, however, these results indicate relatively minor phenotypic variations consequent to VOCs' emission under the stress conditions tested.…”
Section: Isoprene and Ocimene Emission Resulted In A Moderate Toleransupporting
confidence: 91%
“…However, independent studies demonstrated that the emission of isoprenoids led to an increased biomass, leaf area, and pigment content in several species (e.g., [25,34]), which is consistent with our data, suggesting the existence of a tight but complex relationship between isoprene/monoterpene emission and growth. In Zuo et al [34], Arabidopsis plants transformed with a Eucalyptus globulus IspS gene had a higher leaf area, leaf number, and final dry weight than the wild-type Col-0, consistent with our data on both isoprene and ocimene emitters. Similarly, in Loivamäki et al [25], Arabidopsis lines transformed with an IspS gene from gray poplar had higher growth rates under optimal growth conditions.…”
Section: Hemi-and Mono-terpene Emission Improves Plant Growth Under Osupporting
confidence: 92%
See 3 more Smart Citations